Socio-educational support opportunities for young job emigrants in the context of another cultural environment - Radzevičienė, Liuda; Baranauskienė, Ingrida (Social Welfare: Interdisciplinary Approach, 2015)
One of the main reasons of emigration of young people is a lack of opportunities to realize their own potential, to state themselves as full valued individuals. In this aspect, problems of emigration appear in the areas of social work and socio-educational support. Problems of social or socio-educational support are discussed and presented not enough, concerning young job immigrants in theoretical and practical levels, as well. In the most cases the respondents have mentioned friendly and positive relationships with people of the same nationality and with people of different nationalities as well: together organized leisure activities, celebrations, holidays. Research data analysis shows that mostly job centres help immigrants to deal with job search and with consultations as well. On the other hand, it is obvious that young job immigrants are coming to other country to their relatives or friends who have emigrated earlier and have organized their living conditions quite well. Generalizing the research results the activities of a social worker or social pedagogue that are needed for young job emigrants during integration process in changed socio-cultural environment could be defined: it is support during adaptation period, support in the process of job search, legal, educational and health support, as well as organization of cultural activities for immigrants.
Keywords: emigration; young people; socio-educational support